Pengaruh Model Discovery Learning terhadap Kemampuan Komunikasi Matematis Siswa - Etia Etia; Pentatito Gunowibowo; Agung Putra Wijaya (Limacon: Journal of Mathematics Education, 2019)
This quasi-experimental research aimed to find out the influence of discovery learning model towards students’ mathematical communication skill. The population in this research were all students of grade 7th of SMPN 20 Bandarlampung in academic year of 2018/2019 that consist of 352 students and distributed into ten classes. Through cluster random sampling technique, VII B class consist of 30 students and VII D class consist of 32 students were chosen as the research sample. This research used the randomized pretest-posttest control group design. The research data were obtained by the essay test of mathematical communication skill on topic of quadrilaterals and triangle. The analysis of research data used the Mann-Whitney U test. Based on the results of research and discussion, it concluded that discovery learning model was influence towards students’ mathematical communication skill.